Evaluation of wound healing activity of atranorin, a lichen secondary metabolite, on rodents - Barreto,Rosana S. S. (2013)
The aim of this study was to investigate the wound healing activity of atranorin cream (Patent requested) on excision wounds. Seventy-two male rats were anesthetized and an excisional wound was performed. Then the rats were randomly assigned into three groups: untreated control group; atranorin 1 (group treated with 1% AT ointment); and atranorin 5 (group treated with 5% AT ointment). Six animals of each group were euthanized 3, 7, 14 or 21 days after surgical procedures and the wounded areas were analyzed and removed. Serial histological sections were obtained and stained by histochemical techniques (Hematoxilin-Eosin-HEand Sirius red) and immunohistochemical techniques. Topical application of atranorin reduced wound areas, induced earlier granulation tissue formation, increased cell proliferation, improved collagenization and modulated the myofibroblasts differentiation when compared to control animals. It is suggested that atranorin modulates the wound healing process. These data suggest that this formulation based on atranorin extracted from Cladina kalbii AHTI may be a new biotechnological product for wound healing clinical applications.